Floquet topological phase transitions in 2D Su–Schrieffer–Heeger model: interplay between time reversal symmetry breaking and dimerization - Adrian Pena; Bogdan Ostahie; Cristian Radu (New Journal of Physics)
We theoretically study the 2D Su-Schrieffer-Heeger model in the context of Floquet topological insulators (FTIs). FTIs are systems which undergo topological phase transitions, governed by Chern numbers, as a result of time reversal symmetry (TRS) breaking by a time periodic process. In our proposed model, the condition of TRS breaking is achieved by circularly polarized light irradiation. We analytically show that TRS breaking is forbidden in the absence of second order neighbors hopping. In the absence of light irradiation, we identify a symmetry-protected degeneracy and prove the appearance of a flat band along a specific direction in the momentum space. Furthermore, we employ a novel method to show that the four unit cell atoms, in the absence of irradiation, can be interpreted as conserved spin states. With the breaking of TRS via light irradiation, these spin states are no longer conserved, leading to the emergence of chiral edge states. We also show how the interplay between the TRS breaking and dimerization leads to some complex topological phase transitions. The validity of our findings is substantiated through Chern numbers, spectral properties, localization of chiral edge states and simulations of quantum Hall transport. Our model is suitable not only for condensed matter (materials), but also for cold gases trapped in optical lattices or topolectrical circuits.